Determining the fuel ion ratio for D(T) and T(D) plasmas at JET using neutron time-of-flight spectrometry. (1st May 2022) - Eriksson, B; Conroy, S; Ericsson, G; Eriksson, J; Hjalmarsson, A; Ghani, Z; Carvalho, I S; Jepu, I; Delabie, E; Maslov, M; Lennholm, M; Rimini, F; et al.
Abstract: The fusion fuel ion ratio, n T / n D, is an important plasma parameter that needs to be tuned to maximize the power of a tokamak type fusion reactor. It is recognized as a parameter required for optimizing several ITER operating scenarios, and will likely be continuously monitored in future high-performance fusion devices such as DEMO. Tritium was recently introduced in the Joint European Torus (JET) plasma for the first time since the 1997 DTE1 and 2003 TTE campaigns, enabling the possibility to investigate fuel ion ratios. We present a method for measuring n T / n D using neutron time-of-flight (TOF) spectrometry. By fitting the measured neutron spectral features, the relative reaction rate intensities between different ion species can be inferred, from which the fuel ion ratio can be extracted for a corresponding modeled reactivity. Unlike previous measurements of n T / n D using neutron spectrometry, we utilize the neutron energy continuum produced in the three-body TT reaction to determine the fuel ion ratio for plasmas with large concentrations of tritium. Furthermore, the use of neutron TOF spectrometry has never previously been demonstrated for evaluating n T / n D . The method is applied to TOF spectra acquired with TOFOR (JET name KM11) and shown to be consistent with the optical JET diagnostic KT5P which uses optical spectroscopy of a modified Penning gauge plasma to measure tritium and deuterium concentrations in the divertor exhaust gas.